Revolution in Poetic Language - Kristeva, Julia 1941- (New York Columbia University Press, 1984)
The linking of psychosomatic to literary and literary to a larger political horizon raises the question of conservative premises to linguistic, pyschoanalystic, philisophical, and literary theories and criticisms of such.
Abridged translation of the original edition of 1974
Keywords: 19th Century (1801-1900); Literature; Semiotics; France